The debt maturity of Portuguese SMEs: the aftermath of the 2008 financial crisis - Costa, Sérgio; Laureano, L.; Laureano, Raul M. S. (10th International Strategic Management Conference (Procedia - Social and Behavioral Sciences), 2014)
The purpose of this empirical work is to understand the reasoning behind debt maturity choices from Portuguese SMEs after the 2008 financial crisis and to see if those choices are in accordance with the existing literature. We use a sample of 2,000 Portuguese SMEs for the time period of 2009 to 2011. We find an increasing trend on the average debt maturity during the three years analyzed. Our results are partially consistent with the liquidity theory where intermediate quality firms choose to issue more long term debt while high quality firms tend to issue more short term debt. Smaller firms, those more affected by asymmetric information, tend to use debt of shorter maturities. Furthermore, we find evidence supporting the clientele argument where firms affected by higher tax rates have longer debt maturities. Finally, firms with more growth opportunities are using more short term debt.